Prevention of long-lasting atrial fibrillation through antitachycardia pacing in 584 dual-chamber pacemaker patients. (25th November 2020) - Boriani, G; Sakamoto, Y; Iacopino, S; Komura, S; Pieragnoli, P; Minamiguchi, H; Infusino, T; Noma, T; De Rosa, F; Takahashi, Y; Biffi, M
Abstract: Background: Atrial fibrillation (AF) is a frequent arrhythmia in pacemaker patients and is associated with poor quality of life and increased risks of heart failure, dementia, stroke, and death. The MINERVA trial has shown that the combination of 3 pacing algorithms – 1) atrial antitachycardia pacing (aATP), 2) atrial preventive pacing and 3) managed ventricular pacing (MVP) - delays progression to persistent and permanent AF, compared with standard DDDR pacing mode and with MVP mode, in pacemaker patients with AF history. Purpose: We performed a comparative non randomized evaluation to confirm the hypothesis that aATP is the main driver of persistent/permanent AF reduction independently on the effect of preventive atrial pacing. Methods: Thirty-one Italian and Japanese Cardiology centers included consecutive dual-chamber pacemaker patients with AF history. aATP was programmed in all patients while preventive atrial pacing was not enabled. Comparison was made with all the 3 groups in MINERVA randomized trial. The main endpoint was incidence of AF longer than 7 consecutive days, as detected by device diagnostics. Results: A total of 146 patients (73 years old, 54% male) were included and followed for a median observation period of 31 months. The 2-year incidence of AF>7 days was 12% in the aATP group, very similar to that found in the arm of the MINERVA trial with aATP enabled (13.8%, p=0.732) and significantly lower than AF incidence found in the MINERVA Control DDDR arm (25.8%, p=0.012) and in the MINERVA MVP arm (25.9%, p=0.025). Conclusions: In a real-world population of dual-chamber pacemaker patients with AF history, use of aATP was associated with low incidence of persistent AF during follow up, highlighting that the positive results of the MINERVA trial are related to the effectiveness of aATP rather than to the effects of preventive atrial pacing. Funding Acknowledgement: Type of funding source: None